Herramientas didácticas utilizadas por el docente informático y su incidencia en el aprendizaje de los estudiantes de la escuela "María Paulina Solís" de la provincia de Zamora Chinchipe, cantón Yantzaza, periodo lectivo 2013 – 2014. Lineamientos alternativos - Morocho Marín, Luis Antonio (2015)
This thesis refers to: TEACHING TOOLS USED BY THE COMPUTER TEACHER AND ITS IMPACT ON STUDENT LEARNING SCHOOL "MARÍA PAULINA SOLÍS" OF THE PROVINCE OF ZAMORA CHINCHIPE, CANTON YANTZAZA, LECTIVO PERIOD 2013 - 2014, held in According to the provisions of the Rules of Academic System of the National University of Loja. He was raised as General Objective: To determine the incidence of the use of teaching tools Teaching Computer in student learning school "Maria Paulina Solís" of the Province of Zamora Chinchipe, Canton Yantzaza, academic year 2013-2014. The methods used for the preparation of this research work were: Inductive, Deductive, Descriptive, Statistical Model, the same that served as aid to achieve efficiently the proposed goal, with the help of various techniques and instruments such as the interview was applied to professor of computer science subject, the survey to students from the school of basic education "Maria Paulina Solis" to determine the teaching resources and its impact on learning. It is concluded that: 74% of students surveyed indicated that teachers rarely uses multimedia tools support or other software to support teaching, 93%, believes that teachers have sufficient knowledge to manage software and apply Classroom properly, and the teachers interviewed said that using all available tools such as projector, computer, books, texts or films, etc. It is also deduced that: In 55% of the interviewed students they understand the computation class and in 45% that rarely understand the class, being this I finish a considerable percentage of students that you/they don't learn in a correct way this due to the lack of didactic virtual tools as multimedia, with those that it doesn't prepare the educational of computation of the school.